Blast-induced damaged zone studies : Final Report to Trafikverket - Saiang, David (Luleå tekniska universitet, Geoteknologi, 2011)
This report is a summary and conclusions from the study on Blast-Induced Damage around underground excavations in hard rock, which was carried out as a PhD research project by the author. The project was funded by Vägverket and the research was conducted at the Division of Mining and Geotechnical Engineering at Luleå University of Technology. The work resulted in several publications; a PhD thesis, journal articles, conference articles and technical reports. The publications can be downloaded from: http://www.ltu.se/staff/d/davsai?l=en. This final report is compilation of the important elements from these various publications.Because the Blast-Induced Damaged Zone (BIDZ) is generally perceived to have a negative impact on the economics and performance of a tunnel many studies have been conducted to delineate the extent of the BIDZ. The primary goal has been to device ways to control or minimise the extent of this zone. As a result guidelines have been developed by concerned authorities, such as for example AnläggningAMA-98 (1999), to control the extent of BIDZ during tunnel construction. These guidelines however do not give recommendations about the strength and stiffness properties of the BIDZ, which are the most important parameters that control its behaviour and ultimately influence the stability and performance of tunnel.The extent of the BIDZ in majority of the practical cases varied between 0.1 and 1.0 m, with an average ranging from 0.3 m to 0.5 m. The stiffness magnitudes of this zone were as low as 10% to as high as 90% of that of the undamaged rock mass. Field investigation at Kiirunavaara underground mine (Malmgren et al, 2007) showed the stiffness of the BIDZ to vary between 50 and 90% of that of the undamaged rock mass, while the thickness ranged from 0.5 to 1.0 m. Although it was possible to deduce the modulus of the BIDZ the strength however, is the most difficult to measure or estimate. The most generic way to estimate the strength of the BIDZ is the use of a rock mass classification system in ...